Determinants of COVID-19 preventive behaviours among adults with chronic diseases in the USA: an analysis of the nationally representative COVID-19 impact survey - Islam, Jessica Y. (BMJ Open, 2021)
BACKGROUND: Preventive behaviours have been recommended to control the spread of SARS-CoV-2. Adults with chronic diseases (CDs) are at higher risk of COVID-19-related mortality compared to the general population. Our objective was to evaluate adherence to COVID-19 preventive behaviours among adults without CDs compared with those with CDs and identify determinants of non-adherence to COVID-19 preventive behaviours. STUDY DESIGN: Cross-sectional. SETTING AND PARTICIPANTS: We used data from the nationally representative COVID-19 Impact Survey (n=10 760) conducted in the USA. PRIMARY MEASURES: Adults with CDs were categorised based on a self-reported diagnosis of diabetes, high blood pressure, heart disease/heart attack/stroke, asthma, chronic obstructive pulmonary disease (COPD), bronchitis or emphysema, cystic fibrosis, liver disease, compromised immune system, or cancer (54%). RESULTS: Compared with adults without CDs, adults with CDs were more likely to adhere to preventive behaviours including wearing a face mask (χ(2)-p<0.001), social distancing (χ(2)-p<0.001), washing or sanitising hands (χ(2)-p<0.001), and avoiding some or all restaurants (χ(2)-p=0.002) and public or crowded places (χ(2)-p=0.001). Adults with a high school degree or below [Adjusted prevalence ratio (aPR):1.82, 95% Confidence interval (CI)1.04 to 3.17], household income <US$50 000 (aPR:2.03, 95% CI 1.34 to 2.72), uninsured (aPR:1.65, 95% CI1.09 to 2.52), employed (aPR:1.48, 95% CI 1.02 to 2.17), residing in rural areas (aPR:1.70, 95% CI 1.01 to 2.85) and without any CD (aPR:1.78, 95% CI 1.24 to 2.55) were more likely to not adhere to COVID-19 preventive behaviours. CONCLUSION: Adults with CDs are more likely to adhere to recommended COVID-19 preventive behaviours. Public health messaging targeting specific demographic groups and geographic areas, such as adults without CD or adults living in rural areas, should be prioritised.